The Effect of Reverso Online Application on Enhancing Grammar in Narrative Texts: A Study of Eleven-Grade Students at SMAN 1 Palangka Raya - Nadira, Parya; Karani, Elanneri; Misrita (IKIP Siliwangi, 2025)
The research investigates the effectiveness of the Reverso online application in improving grammar in narrative text writing among eleventh-grade students at SMAN 1 Palangka Raya. The study compared the improvement in grammar abilities between the experimental group using Reverso and the control group using conventional methods. Data was collected through pre-test and post-tests, focusing on narrative writing abilities. Normality tests showed significant differences, necessitating non-parametric tests for further analysis. The hypothesis testing results indicated a significant enhancement in the experimental group relative to the control group, with a p-value of .000, which is less than the significance threshold of 0.05, or the post-test of class XI IPS 2 as the experiment group was 93.33 and the post-test of control group XI IPA 4 was 81.40. This suggests that the Reverso application had a positive effect on students' grammar improvement in narrative texts. The study concludes that the Reverso online application is effective in enhancing students' grammar in writing narrative texts. Based on the findings, suggestions are made for teachers to integrate similar technological tools in their teaching practices, for students to practice grammar using educational applications regularly.